KEPASTIAN HUKUM TERHADAP PRINSIP FIRST TO USE DALAM PERLINDUNGAN MEREK TERDAFTAR DI INDONESIA - Susi Marlinda Manurung (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Trademark protection in Indonesia currently applies the first to file principle as stipulated in Article 3 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. However, in practice, the application of the first-to-file principle has not been able to provide legal certainty for trademark owners. As a result, several countries have adopted the first-to-use principle in their trademark protection systems. Although Law Number 20 of 2016 does not explicitly regulate the first-to-use principle, several provisions within the law reflect elements of this principle, including Article 21 paragraph (1), Article 21 paragraph (3), and Article 78 paragraph (1). The application of the first-to-use principle can also be observed in several court decisions in which judges consider the first use of a mark when determining trademark ownership. On the other hand, there are also court decisions that remain consistent with the first to file principle as mandated by the law. This research is a normative legal study analyzed using a qualitative method. The study employs the theory of legal certainty and the theory of legal systems. It concludes that the implementation of the first to use principle in Indonesia is still highly abstract and therefore does not yet reflect legal certainty for trademark owners.Keywords: Trademark, Legal Certainty, First to Use.